2019
DOI: 10.1007/s11069-019-03621-4
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric circulation conditions during winter warm spells in Central Europe

Abstract: The objective of the paper was to characterise the temporal and spatial variability of winter warm spells in Central Europe in the years 1966/1967-2015/2016 and to determine the circulation conditions of their occurrence. The applied data were obtained from the Polish Institute of Meteorology and Water Management, Deutscher Wetterdienst and the National Centre for Environmental Prediction/National Centre for Atmospheric Research. A warm spell was defined as a sequence of at least three warm days, i.e. when the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Existing studies in Central Europe and Eastern Europe focus primarily on hot extremes in summer and remain in agreement that these extremes have been rapidly increasing in terms of frequency, intensity, and spatial range since the mid-20th century [47][48][49][53][54][55]. Considerable changes also occur in these two regions in winter [66]. Our results indicate that changes in winter manifest themselves particularly strongly in terms of a large increase in TXx as well as a substantially higher frequency of occurrence of very severe ETEs in recent decades.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Existing studies in Central Europe and Eastern Europe focus primarily on hot extremes in summer and remain in agreement that these extremes have been rapidly increasing in terms of frequency, intensity, and spatial range since the mid-20th century [47][48][49][53][54][55]. Considerable changes also occur in these two regions in winter [66]. Our results indicate that changes in winter manifest themselves particularly strongly in terms of a large increase in TXx as well as a substantially higher frequency of occurrence of very severe ETEs in recent decades.…”
Section: Discussionmentioning
confidence: 86%
“…Kivinen et al [63] obtained similar results for the Northern Fennoscandia for the period 1914-2013, and determined the occurrence of a much higher number of extremely warm days in April and October over the last 20 years of the study period. Chapman et al [65] examined the Central England Temperature Record and found a two-to threefold increase in the frequency and duration of winter warm spells since the late 1800 s. Significant increasing trends in the number of warm winter days were also noted for Central Europe [66] as well as for high mountain sites in the Swiss Alps [67]. Research results for Southeastern Europe vary.…”
Section: Introductionmentioning
confidence: 99%
“…In the Northern Hemisphere, warm spells during winter have increased in duration and/or frequency, e.g . throughout eastern Canada (Shabbar & Bonsal 2003), in Europe (Tank et al 2002; Tomczyk et al 2019) and in the Swiss Alps (Beniston 2005). Concomitantly, winters are warming and shortening and experiencing reduced snowfall and increased rain with climate change (IPCC 2013).…”
Section: Introductionmentioning
confidence: 99%
“…(2020). The increase in wintertime air temperature in Central Europe has been detected by Tomczyk et al (2019), however most of these changes were statistically insigni cant. In this study, large-scale WSs have been associated with the advection of warm air masses and anomalies in geopotential height in the entire troposphere, with the largest anomalies at 250 hPa several days before the extreme event.…”
Section: )mentioning
confidence: 99%